Konsep Pembinaan Manusia: Telaah Pemikiran Ibnu Sina (370-428 H) dalam Kitab al-Siyāsah - Iskandar, Iskandar; Azwar, Azwar; Samsuddin, Samsuddin (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This research aims to examine Ibn Sina's concept of coaching in the book al-Siyāsah, especially the five aspects that Ibn Sina highlights, namely the concept of self-cultivation, the concept of financial management, the concept of family coaching, the concept of child coaching, and the concept of coaching servants. This research is a type of library research using descriptive qualitative methods with a historical and social approach. The results of this research show several things. First, Ibn Sina views that the first thing a person must pay attention to is himself (siyāsatu nafsihi) because if a person succeeds in getting around (managing) himself, then he will have no difficulty in managing those above him. Second, in economic and financial matters, Ibn Sina emphasized that whoever wants a profession to meet his needs, he should try to pursue it until he continues to develop (taqaddum) and become an expert in that field and really emphasizes the aspect of itqān (professionalism) in pursue a job. Third, in family development, Ibnu Sina emphasized the importance of the position of pious women as partners for men who have the characteristics and muwaṣafāt as recommended by the Prophet Muhammad. Fourth, in terms of child development, Ibn Sina believes that parents must choose good names for their children, then choose and provide mothers for them, so that they do not grow up to be stupid, stupid and disabled children, alienating their children. their children from bad morals and turning them away from despicable habits. Fifth, Ibn Sina stated that the relationship between a servant and an employer is like the relationship between a member of the body and the whole body. Therefore, Ibn Sina suggested that employers should be grateful to Allah who has subdued them (taskhir).